Data, diagnoses, and nursing interventions focused on a person living with an ostomy: scoping review protocol - Carla Regina Rodrigues Silva; Maria Alice Brito; Abel Paiva Silva; Carmen Queirós; Ernesto Jorge; Fernanda Bastos (Instituto Politécnico de Viseu, 2023)
Introduction: The building of an ostomy generates changes that trigger a health/disease transition. Nurses play a major role in adapting to the new condition. It is important to formalize nursing knowledge that supports nurses' decision-making in order to incorporate it into information systems that promote evidence-based nursing practice. Objetive: Continuously map the nursing knowledge involved in the process of care planning, focusing on the person living with an ostomy. Methods: Joanna Briggs Institute's scoping review guidance and, the Cochrane Collaboration's guidance on living systematic reviews will be followed to meet the review's objective. Two independent reviewers will evaluate the relevance of the articles, the extraction and synthesis of the data. Studies published in English, Spanish and Portuguese from 2009 onwards, searched in MEDLINE (PubMed), CINAHL (EBSCO), Scopus, JBI Library of Systematic Reviews and Cochrane Central Register of Controlled Trials, OpenGrey, RCAAP and Dart-Europa will be included. Results: It is expected to map the data, diagnoses and nursing interventions centered on the person living with an ostomy, allowing the formalization of the knowledge involved in the design of nursing care for this population group. Conclusion: This scope review will show trends that will support nurses' decision making in order to improve the quality of clinical practice.